2014
DOI: 10.1126/scitranslmed.3008325
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop neuromodulation of spinal sensorimotor circuits controls refined locomotion after complete spinal cord injury

Abstract: Neuromodulation of spinal sensorimotor circuits improves motor control in animal models and humans with spinal cord injury. With common neuromodulation devices, electrical stimulation parameters are tuned manually and remain constant during movement. We developed a mechanistic framework to optimize neuromodulation in real time to achieve high-fidelity control of leg kinematics during locomotion in rats. We first uncovered relationships between neuromodulation parameters and recruitment of distinct sensorimotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
178
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 44 publications
8
178
0
Order By: Relevance
“…Since the SCS-induced motor outputs are composed of series of stimulus-triggered PRM reflexes Minassian et al 2004), the stimulation frequency entrains the motoneuron firing rate and thus critically influences the muscle force produced. This relationship between the stimulation frequency and muscle force was also used in a recent study to achieve control of hindlimb kinematics during SCS-induced locomotion in paralyzed rats (Wenger et al 2014). The phenomenon described in the present report shows that, under specific conditions, the effective output frequencies (given by the larger-amplitude responses within the periodic modulation) may be lower than the stimulation frequency applied.…”
Section: Discussionmentioning
confidence: 68%
“…Since the SCS-induced motor outputs are composed of series of stimulus-triggered PRM reflexes Minassian et al 2004), the stimulation frequency entrains the motoneuron firing rate and thus critically influences the muscle force produced. This relationship between the stimulation frequency and muscle force was also used in a recent study to achieve control of hindlimb kinematics during SCS-induced locomotion in paralyzed rats (Wenger et al 2014). The phenomenon described in the present report shows that, under specific conditions, the effective output frequencies (given by the larger-amplitude responses within the periodic modulation) may be lower than the stimulation frequency applied.…”
Section: Discussionmentioning
confidence: 68%
“…There is recent promising evidence demonstrating recovery of stepping in rats with a transected spinal cord after a combinatorial approach incorporating locomotor training with electrical neuromodulation and a pharmacology agent. 10 There have not been many practical efforts in this direction in humans, however.…”
Section: Introductionmentioning
confidence: 99%
“…SCI often leads to serious neurological sequelae and medical complications. Therefore, more efforts in medical practice development are needed to improve the quality of life of patients with SCI.It has been reported that SCS in lumbosacral segments helped restore voluntary control of locomotion in paralyzed rats after SCI [57].A study using closed-loop neuromodulation to treat rats with complete SCI found that it improved the locomotion and enabled animals to perform more than 1,000 successive steps without failure and to climb staircases of various heights and lengths with precision and fluidity [58]. Another similar study on rats, however, found no treatment effect [59].…”
Section: Neuromodulation For Spinal Cord Injurymentioning
confidence: 99%